2018
DOI: 10.1111/jopy.12362
|View full text |Cite
|
Sign up to set email alerts
|

Let it go: Relationship autonomy predicts pro‐relationship responses to partner transgressions

Abstract: This research provides consistent and compelling evidence that the degree of self-determination underlying commitment is important for understanding how people respond to transgressions in their relationships, beyond their current levels of commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Autonomous and controlled motivation may be particularly relevant for understanding daily fluctuations in well-being in committed relationships. In a study of responses to partner transgressions, people who endorsed more autonomous reasons for being in their relationship were more likely to forgive partner transgressions over a 5-week period (Hadden et al, 2017). Additionally, on weeks when people reported higher autonomous relational motivation, they were more likely to forgive partner transgressions in comparison to weeks when it was lower.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Autonomous and controlled motivation may be particularly relevant for understanding daily fluctuations in well-being in committed relationships. In a study of responses to partner transgressions, people who endorsed more autonomous reasons for being in their relationship were more likely to forgive partner transgressions over a 5-week period (Hadden et al, 2017). Additionally, on weeks when people reported higher autonomous relational motivation, they were more likely to forgive partner transgressions in comparison to weeks when it was lower.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…The finding that actor's autonomous relationship motivation promoted relationship goal progress represents an important contribution to RMT. To date, studies examining RMT have shown that relationship autonomy contributes to positive relational behaviors (Blais et al, ), increased personal happiness in the relationship (Blais et al, ), greater understanding and reduced defensiveness in conflicts (Knee et al, ), increased relationship satisfaction (Knee et al, ), pro‐relationship responses to partner transgressions (Hadden, Baker, & Knee, ), and higher quality caring and support (Hadden, Rodriguez, Knee, & Porter, ). This study extended the benefits of relationship autonomy in romantic couples to greater progress in the pursuit of relationship goals.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 15 eligible research items, 7 items were unique (i.e., the other 8 were overlapping: for instance, a finding that was both presented as a poster and published in a manuscript). The seven research items, in turn, contributed 116 dyadic cross-sectional estimates from 12 separately reported studies (Baker, Chopik, & Nguyen, under review;Baker, Nguyen, Knee, & Petit, 2018;Haddad et al, 2016;Hadden, Baker, & Knee, 2018;Hadden, Rodriguez, Knee, DiBello, & Baker, ;Rodriguez et al, 2019).…”
Section: Selected Studiesmentioning
confidence: 99%